Virtual inclusion through telepresence robots: an inclusivity model and heuristic - Charteris, Jennifer; Berman, Jeanette; Page, Angela (International Journal of Inclusive Education, 2022)
This article leverages existing literature around the use of telepresence robots to provide a conceptualisation of virtual inclusion. Telepresence involves the use of mediating technology to generate connection with others in a remote context. Recent developments have seen telepresence robots used to create a sense of ‘being there’ when the person’s physical presence is not possible. Telepresence robots can provide children with the capability to maintain an embodied experience in schooling locations when they are absent due to chronic illness. Through building their knowledge of integrating this technology into their pedagogy, teachers can support students to engage in classroom activities through real-time virtual communication. The article extends what is known about how telepresence robots can be used for virtual inclusion and what the challenges and considerations are for the use of telepresence robots in schools. Technological, physical, social and pedagogical aspects of telepresence robots use for virtual inclusion are detailed with heuristic for introducing them into schools.
Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2022.2112769